IMPROVEMENTS IN INJURY PREVENTION BEHAVIOURS OF RUGBY UNION PLAYERS ASSOCIATED WITH BOKSMART INTERVENTION PROGRAMME. Issue 7 (11th March 2014) - Brown, J; Lambert, M; Lubbe, S; van Mechelen, W; Verhagen, E
Abstract : Background: Rugby union ("rugby") players have an above-average risk of injury compared to participants of other popular team sports. Player behaviour has been identified as a critical area of injury prevention, yet understudied. Objective: To assess whether rugby player behaviour improved over the concomitant time period of the BokSmart nationwide injury prevention programme. Design: An anonymous knowledge, attitude and self-reported behaviour questionnaire was completed by tournament players on a yearly basis from 2008-2012. A generalised linear model assessed whether the proportion of "correct" injury-prevention behaviour improved over this five year period. Setting: Junior (under-18) and senior (adult) annual rugby tournaments. Participants: Of the 112 junior and 84 senior teams, 111 (99%, n=2279 players) and 81 (96%, n=1642 players) teams opted to complete the questionnaire. Assessment of risk factors: Besides age, team and year (of tournament): "perceived necessity of a coach safety course–yes/no", "injury prevention role of coaches/referees/players–yes/no" (role), "previous injury–yes/no (injury)", "ethnicity" and "position - forward/back" were considered as behavioural determinants. Main outcome measurements: The assessed behaviours were mouthguard use, warming-up/cooling down, injury management (ice, compression, elevation, heat, alcohol, massage, exercise), techniques (scrum, tackle, ruck) and physical conditioning. Results: Five of the 18 self-reported behaviours improved significantly (P<.005) between 2008–2012: mouthguard use (practice–36% and matches–28%), cooling down after practice/matches (32% each) and elevating injured limbs (36%). Other behaviours remained unchanged. Other important determinants of other behaviours were team and age. Conclusions: No behaviours worsened, while five of the injury prevention behaviours have improved since the launch of BokSmart (mid 2009–present). Future studies should ascertain whether the BokSmart programme had a causal effect on the improved behaviours and whether BokSmart is able to improve the remaining behaviours.